PEMBUATAN PETA DIGITAL DESA WONOHARJO BERBASIS QR CODE “DIGITAL MAP WONOHARJO VILLAGE BASED ON QR CODE” - Widijanto, Hery; Danu Prihanto, Hendrawan; Ainun Syah Alfarizi, Ilham; Naufal Ramadhan, Muhammad (Inisiasi, 2024)
Wonoharjo Village is located in Nguntoronadi District, Wonogiri Regency ,Central Java, which has alot of potential in agriculture and water .Wonoharjo Village does not yet have a digital map, characteristic of a developed village. In this activity ,KKN students carried out the activity"Making Digital Maps of Wonoharjo Village Based on QR Code."The activity aims to realize a digital map of Wonoharjo village. This Digital Map is created using the ArcGis application and soft data files needed for digital map viewing. The activity was also equipped with socialization on how to apply the resulting digital map. The activity results are in the realization of a digital map of Wonoharjo Village and are expected to help realize Wonoharjo Village with Smart Governance. Digital maps can make it easier for anyone who wants to access information about Wonoharjo Village, which can help in developing tourism and village development.